Influencia de los medios de comunicación en la elección ciencias-letras en bachillerato y universidad. El caso español: análisis del periodo 1988-2001 - Elías Pérez, Carlos (Estudios sobre el Mensaje Periodístico, 2006)
So many experts consider that really exists a strong scientific careers crisis in western countries. In this study we try to analyze this phenomenon since the point of view of the scientist image in the mass media (movies, press and television). For do it we use the data registration in the Spanish secondary schools and universities since academic year 1988/89 to 2000/2001 and we compared with different news . As a conclusion of this analysis can be indicated that the mass media offer a negative approach to the scientific world. Obviously, mass media are not determinants at the moment of choosing professional options, but all studies in communication theory shows that exists a strong relationships between what we think and what we hear/read/watch in mass media about the world. Perhaps the scientific careers crisis will be only a collateral effect in the decline of science cultural impact at the present times. As a conclusion we could prove there is a relationships between student registration in science/literacy and the problems about sciences careers they can read in newspapers.